PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PERTAMBANGAN - Biharuddin, Ahmad; Hamdun, Edy Kusnadi; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Mining companies on the Indonesia Stock Exchange (IDX) are one of the industrial sector companies that have distinctive characteristics in their financial analysis. Every year there is high demand in the market with limited supply, and commodity prices rise rapidly, even touching record highs. Thus, many investors glance at the mining sector, which makes its share price high. The purpose of this study was to examine the effect of profitability and Leverage in influencing stock Returns moderated by dividend policy. The population of this study is mining companies listed on the IDX 2020-2022. Sampling technique with purposive sampling. Data analysis and hypothesis testing using the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis using the Smart PLS 3.0 application show that Profitability has a significant effect on stock Returns, and Leverage has no significant impact on stock Returns. The results of the indirect effect hypothesis test show that profitability has no significant impact on stock Returns moderated by dividend policy and Leverage has no significant effect on stock Returns moderated by dividend policy.